Peculiar phase diagram with isolated superconducting regions in ThFeAsN1−xOx. (25th May 2018) - Li, Bai-Zhuo; Wang, Zhi-Cheng; Wang, Jia-Lu; Zhang, Fu-Xiang; Wang, Dong-Ze; Zhang, Feng-Yuan; Sun, Yu-Ping; Jing, Qiang; Zhang, Hua-Fu; Tan, Shu-Gang; Li, Yu-Ke; Feng, Chun-Mu; et al.
Abstract: ThFeAsN1− x O x ( ) system with heavy electron doping has been studied by the measurements of x-ray diffraction, electrical resistivity, magnetic susceptibility and specific heat. The non-doped compound exhibits superconductivity at K, which is possibly due to an internal uniaxial chemical pressure that is manifested by the extremely small value of As height with respect to the Fe plane. With the oxygen substitution, the T c value decreases rapidly to below 2 K for, and surprisingly, superconductivity re-appears in the range of with a maximum of 17.5 K at x   =  0.3. For the normal-state resistivity, while the samples in intermediate non-superconducting interval exhibit Fermi liquid behavior, those in other regions show a non-Fermi-liquid behavior. The specific heat jump for the superconducting sample of x   =  0.4 is, which is discussed in terms of anisotropic superconducting gap. The peculiar phase diagram in ThFeAsN1− x O x presents additional ingredients for understanding the superconducting mechanism in iron-based superconductors.